Fibre Optic Readout of Microcantilever Arrays for Fast Microorganism Growth Detection. (13th September 2011) - Maloney, N.; Lukacs, G.; Nugaeva, N.; Grange, W.; Ramseyer, J. P.; Jensen, J.; Hegner, M.
Abstract : We present a fibre-optic-based device for the automated readout of microcantilever arrays for fast microorganism growth detection. We determined the ability of our device to track shifts in resonance frequency due to an increase in mass on the cantilever surface or changes in mechanical stiffness. The resonance frequency response of 7  μ m thick agarose-functionalised cantilevers was tracked as humidity levels were varied revealing a mass responsivity of~ 51 ± 1  pg/Hz. The resonance response of microcantilevers coated with Aspergillus niger (A. niger) spores was monitored for >48 h revealing a growth detection time of >4 h. The growth of mycelium along the cantilevers surface is seen to result in an increase in resonance frequency due to the reinforcement of the cantilever structure. The use of our fibre optic detection technique allows data to be recorded continuously and faster than previously reported.